Abordaje fisioterapéutico en pacientes con artritis reumatoide en el Centro Gerontológico Diurno del Cantón Montalvo. Junio-septiembre 2024. - Castro Párraga, Dayana Fernanda (2024)
Rheumatoid arthritis is a pathology that affects between 0.5% and 1% of the world's population, and is more common in the geriatric population, since the risk of developing the disease increases with age. This systemic disease is mainly characterized by the damage it causes in the joints, which can be intermittent, causing joint destruction, deformity and varying degrees of functional disability in patients who suffer from it. It is important to take into account the difficulties faced by older adults who suffer from chronic pain and lack adequate treatment, which can reduce their life expectancy. The present research was carried out at the Gerontological Day Center of Canton Montalvo, during the period from June to September 2024, with the objective of identifying the physiotherapeutic techniques applied in the management of rheumatoid arthritis in older adults. Referring that physiotherapy treatment includes the use of various methods such as therapeutic exercises, massage therapy, laser therapy and thermotherapy, among others. It is essential to evaluate the degree of functional dependence of patients, which is related to their activities of daily living. The deductive method was used and the research approach was quantitative, descriptive and field, complemented with a bibliographic review. We worked with a sample of 25 older adults suffering from rheumatoid arthritis. The relevant results of this research reveal that the most used techniques in the physiotherapeutic approach for RA are manual therapy and strengthening exercises representing a high efficacy observed in 56% of the cases, the regularity of the physiotherapy sessions was highlighted as the most relevant factor for the effectiveness of the treatment. In conclusion, the techniques used in the center proved to be highly effective in improving the symptoms of rheumatoid arthritis in older adults.